Effect of the Type of Organic Waste and Retention Time on Biogas Production from Cow Dung - Oktavius Yoseph Tuta Mago; M A Yohanita Nirmalasari; Agustina Dua Kuki; Yohanes Nong Bunga; Aljefridus Misa (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2020)
Nowadays, the demand on fossil energy is increasing in number whereas its availability is decrease. People are still reckoned on it, despite of its rareness. Fossil energy utilized must be banned due to its negative effect. It is time for us to use renewable and eco-friendly energy (biofuel). Biogas is one of biofuel produced from anaerobic decomposition of organic matter by microorganisms. Organic waste as a by-product of our daily activities can be used as raw material to produce biogas. To use waste, means to decrease the environmental pollution problem. This research is aim to study the type of organic waste as a raw material to produce biogas through anaerobic digestion and its retention time. Organic wastes that were used in this research are domestic waste (food waste), agriculture waste (corn leaves) and industrial waste (solid and liquid waste of tofu). All of these wastes were mixed with cow dung as the starter/inoculum. As a control, the starter was used without organic waste addition. The testable retention times were 1st week until 9th week. The experimental design was Factorial Complete Randomized Design with confidence level 95%. The result showed that all the type of organic waste can be used to produce biogas through anaerobic digestion. Statistically, the average volume of biogas produced from industrial waste per week, 5794,3 ml was significantly different from any other organic waste (P=0,000). The best retention time was found on 8th week with the average volume of biogas was 3675,6 ml (P=0,006). There was no interaction between these two factors (P=0,1). This research is expected to open the people’s awareness about the management of useable organic waste as a raw material to produce biogas.